Crew Resource Allocation and Manning Management in Indonesian Shipping Companies: A Qualitative Study of Competency-Based Crewing Practices Under STCW Standards - Larsen Barasa; Markus Yando; April Gunawan Malau (International Forum of Researchers and Lecturers, 2026)
Competency-based human resource management in seafarer crewing requires that certification attainment, as standardized through the STCW Convention, translate into deployment decisions genuinely reflecting verified operational competency rather than administrative compliance alone. This study investigates the gap between STCW competency certification and actual competency-based crewing and manning allocation decisions within Indonesian shipping companies. Employing a qualitative design grounded in competency-based human resource management theory and stakeholder theory, the study conducted focus group discussions and semi-structured interviews with twenty-three participants drawn from crewing managers, fleet superintendents, and seafarer welfare association representatives. Data were collected between April 2025 and April 2026. Thematic analysis, cross-group comparison, and narrative synthesis were applied. Findings reveal a dominant certificate-over-competency deployment logic in which crewing decisions are driven primarily by STCW certificate availability and minimum manning schedule compliance rather than by genuine operational competency assessment. Three reinforcing organizational mechanisms sustain this logic: the absence of company-level competency verification infrastructure beyond certificate checking, commercial schedule pressure overriding competency-optimal crewing decisions, and the structural inaccessibility of meaningful seafarer performance history within existing crewing management information systems. The study contributes an organizational diagnosis of the certification-competency gap within Indonesian maritime crewing practice and provides actionable recommendations for company-level and regulatory reform.